RESTORATIVE JUSTICE AND THE SETTLEMENT OF THEFT CRIMES BY ART IN CIREBON: A CASE STUDY AND CRIMINAL LAW PERSPECTIVE - Awanda Handani; Dian Noviyani (Ann Publisher, 2025)
Abstract Background. Article 367 of the Criminal Code (KUHP) regulates the crime of theft in the family. This article also governs theft committed by the person who helps to commit the theft. Theft in the family is a criminal offense of complaint, meaning that it can only be prosecuted if there is a complaint from the aggrieved party. The complaints referred to in this article are complaints against people who commit theft. According to Awdah, Aims. Theft is the act of stealing other people's property. The meaning of stealth is to take it without the knowledge and consent of its owner. Methods. In this study, we use a qualitative approach to the crime of theft that leads to restorative justice (RJ), in-depth interviews The researcher can interview various parties involved in the restorative justice process, such as perpetrators, victims, mediators, and law enforcement officials, to get a clearer picture of the effectiveness of RJ in resolving theft cases. Conclusion. Restorative justice is one of the settlements of a case before it is continued to court by both parties. This restorative settlement cannot be applied to all criminal cases, but it can be used to minor crimes under its provisions. Implementation. The result of this restorative settlement aims to reconcile both parties.